Comparison between traditional strength training and complex contrast training on soccer players - Spineti, J.; Figueiredo, T.; Willardson, J.; Bastos de.; Assis, M.; Fernandes de Oliveira, L.; Miranda, H.; Machado de Ribeiro Reis, V. M.; Simão, R. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: The purpose of this study was to compare traditional strength training (TST) versus complex and contrast training (CCT) on sprint, change of direction speed (COD) and squat jump (SJ) in young male soccer players. METHODS: Twenty-two soccer players (age: 18.4±0.4 years, body mass: 70.2±9.1 kg, height: 179.9±7.5 cm), were randomly assigned to one of two groups: TST (N.=12) and CCT (N.=10). The study was conducted using a randomized experimental design over an eight-week period. The participants assigned to the CCT group performed high-power exercises paired with high-velocity exercises. The participants assigned to the TST group performed resistance exercises in a straight-set forma. During the study period, sprint tests for 5, 10, 20 and 30 m split times, COD and SJ were applied. A two-way ANOVA was applied, and the alpha level was P<0.05. RESULTS: The results demonstrated that the CCT regimen elicited significant within-group differences in 5 m sprint time (1.032 s to 0.997 s, pre- and postintervention, respectively, effect size (ES) = -0.5, medium; P=0.04), COD (5.963 s to 5.639 s, pre- and postintervention, respectively, ES -2.7, large; P<0.001) and SJ (30.9 cm to 34.4 cm, pre- and postintervention, respectively, ES =0.8, large; P<0.001). Conversely, the TST did not elicit significant within-group differences for any of the dependent variables. No differences were found between groups at the post-test time point. CONCLUSIONS: In conclusion, the CCT protocol could be used to improve sprint, COD and SJ in male soccer players.